Biophysical interactions in the Iceland Basin - Harington, Amy (Department of Biological Sciences, 2017)
The Iceland Basin in the N. Atlantic has attracted considerable recent attention because the spring bloom in this region acts as the most powerful biological carbon pump anywhere in the world oceans. Furthermore, the link between primary productivity and herbivory by the calanoid copepod, Calanus finmarchicus provides the trophic link between primary producers and the important commercial fishery for Atlantic Cod. However, one result of ocean warming is that the distribution of the cold water loving Calanus finmarchicus is being pushed northwards which adversely affects the food supply to juvenile Cod. Perhaps of more serious concern are concerns that the biological carbon pump may weaken as a result of increased thermal stratification and therefore reduce upward nitrate flux to drive nitrate-based export production. This was in fact confirmed at least in the study region which is dominated by regenerated production (f-ratio <0.5) which in turn suggests a shift in community structure from larger celled organisms to smaller celled organisms, characterised by long inefficient food chains. This project makes use of summer cruise data to the Iceland Basin last summer (2007) where measurements of 15N derived new production (NP) were made to add to previous seasonal (spring, winter) measurements of NP in the region.